2003
DOI: 10.1046/j.1469-0691.2003.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Bacteroides fragilis group isolates in Europe

Abstract: Antimicrobial resistance among the B. fragilis group is increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 34 publications
(65 reference statements)
9
56
2
2
Order By: Relevance
“…Although some Bacteroides spp. are suppressed by clindamycin (Sullivan et al, 2003), others have been shown to be resistant to clindamycin and several other antibiotics (Hedberg and Nord, 2003;Lö fmark et al, 2006) and resistance to this antibiotic is increasing (Hedberg and Nord, 2003). Previously, we found that 7 days administration of clindamycin resulted in a dramatic increase in antibiotic resistant Bacteroides spp.…”
Section: Introductionmentioning
confidence: 83%
“…Although some Bacteroides spp. are suppressed by clindamycin (Sullivan et al, 2003), others have been shown to be resistant to clindamycin and several other antibiotics (Hedberg and Nord, 2003;Lö fmark et al, 2006) and resistance to this antibiotic is increasing (Hedberg and Nord, 2003). Previously, we found that 7 days administration of clindamycin resulted in a dramatic increase in antibiotic resistant Bacteroides spp.…”
Section: Introductionmentioning
confidence: 83%
“…Frequently, the other species in the B. fragilis group are more resistant than B. fragilis to many antibiotics. Current antibiograms of anaerobic bacteria have been summa-rized and reviewed recently (114,115,256,258) and results of several studies have been collated in Table 3.…”
Section: Susceptibility Patterns Of Bacteroidesmentioning
confidence: 99%
“…The antimicrobial susceptibilities of some members of the B. fragilis group vary, especially to the second-and third-generation cephalosporins. B. fragilis is generally the most susceptible, and B. thetaiotaomicron and Parabacteroides distasonis generally are more resistant (87,88).…”
Section: ␤-Lactam Antibioticsmentioning
confidence: 99%